Trabalho, educação e desenvolvimento: o norte da educação da CUT na Amazônia - Silva, Gilmar Pereira da (2006)
This thesis is the result of a bibliographic and field research, with the purpose to answer in what way the process of education developed by the CUT, expressed in the experience of the Project Vento Norte, developed in the Amazônia has colaborated in the sense of the possibility of a articulation between work, education, and develpoment. The bibliographic reasearch was based in the studies of theoreticals like Gadotti (1999), Marx (1998, 1998a), Pochman (2002), Brandão (1985, 2002), Adorno (1999, 2000), Horkeimer (1976), reseachers that in the process of their studies, thinked about the theme, related to work, to education and to developement. The field research was done by the intervews with CUT s educators and managers from the states of Acre, Amazonas, Amapá, Pará, Rondônia and Roraima. The thesis s process of elaboration is done in a cobweb of elements articulated to socioculture values from the habitat of amazônia people. The conclusions point to us that the hypothesis of the CUT, by the Project Vento Norte, develops a propose of education that articulates Work, Education and Development that is confirmed. But, the partiality of the project is presented by the limitations of the CUT s possibility in continuation of the project. Thats why the thesis suports the idea of the project and it consolidation in the Amazônica Region, by the conception of the syndicate managers and educators